The Use of English Video to Improve Listening Comprehension of Vocational Students of Bengkalis State Polytechnic - M.I. Gunawan; Aswandi (ABEC Indonesia, 2023)
Based on the problems found in the classroom, the students at State Polytechnic of Bengkalis had problems in comprehending listening business text material. It seemed difficult for them to understand and to identify the material of the oral text. They also had limited vocabulary. Therefore, the researcher decided to solve these problems by using English video as learning media. The research aimed at finding out to what extent English Video could improve the students’ Listening comprehension skill. This Strategy application research was conducted in two cycles. Each cycle consisted of four meetings; three meetings for teaching listening comprehension and one meeting was for the test. Participants of the research were 17 students of English department. There were some instruments used as data collection were (1) observation sheets; students, teacher, and teaching steps (2) field notes (3) and reading comprehension tests. The research findings showed that the English video could improve the students’ listening comprehension. It could be seen from the improvement of the students’ score in listening comprehension of Business texts test. The average score of students in cycle 1 was 65 and in cycle 2 was 68. In conclusion, the implementation of English Video could improve the students’ listening comprehension of Business texts at English Department Students of State Polytechnic of Bengkalis. It improved both students’ score in Listening tests and their interest in reading activities